Rational recovery model of depot processing equipment at the industrial enterprise - Kapitsa, M. I.; Hryshechkina, T. S. (Science and Transport Progress, 2014)
Purpose. The problem of the maximum resources recovery of rolling stock repair depot of industrial enterprise with limited resources consumption, which are used in the system is today’s topical question.The main factors that affect the repair depot operation of industrial enterprise are reviewed. The most significant factors, affecting the quality of the repair depot, are emphasized for further study, specifically - the state of the major repair equipment of a sector. There is a need to minimize the impact of the unsatisfactory state of this factor. Methodology. The formed task of major equipment rational repairing in the mathematical sense is based on the solution of a vector optimization problem. In this case the target functions are the monetary funds spending and time expenditure for repairing. Findings. The mathematical model of optimal equipment maintainability of the repair department at the industrial enterprise was developed by the authors. On the example the choice model of optimal path for equipment repairing of enterprise repair department is described. Originality. As a result of the conducted research the repairing system of major equipment of industrial enterprise sectors was improved. As the mathematical model of rational system recovery of industrial enterprise repair depot we recommend apparatus of class problems of vector optimization. Practical value. Using the proposed model of major equipment repair system of the repair depot at the industrial enterprise will improve the quality of the department by increasing the efficiency of primary resources - time and monetary funds - which are spent by the sector in order to repair its techniques.